Penerapan Metode Omnibus Law dalam Pembentukan Peraturan Daerah pada Pemerintahan Kabupaten Cianjur - Taufiq Ismail; Sahid Jayadi Hamzah (Jurnal Hukum Lex Generalis, 2025)
This study discusses the application of the omnibus law method in the formation of regional regulations (perda) in Cianjur Regency as a strategic effort in organizing regional regulations that tend to overlap, have multiple interpretations, and are inconsistent. The purpose of this study is to identify the urgency and mechanism for using the omnibus law method in the formation of regional regulations to support synchronization and harmonization with higher laws and regulations, especially after the enactment of the Job Creation Law. This study uses a normative legal approach with conceptual and historical analysis of applicable legal provisions. The results of the study show that the omnibus law method is effective in simplifying regional legal products through the consolidation of various related perda into one more comprehensive regulation. The implementation mechanism includes the formation of a drafting team, inventory, grouping of content materials, to the formal legislative process through the regional regulation formation program (Propemperda). Although this method offers regulatory efficiency, challenges are still faced, especially the absence of technical implementing regulations from the central government which has the potential to cause formal legal problems in the future. Therefore, further policies are needed that guarantee legal certainty in the application of the omnibus law method at the regional level.